The role of reactive oxygen species in the pathogenesis and treatment of endometrial cancer - Lee, Jeongmin; Yeo, Seung Geun; Lee, Jae Min; Kim, Sung Soo; Jeong, You Jeong; In Oh, Tong; Park, Dong Choon (Frontiers in Medicine, 2025)
Reactive oxygen species (ROS) play dual roles in the pathophysiology of endometrial cancer (EC). Oxidative stress induced by ROS can promote the survival and proliferation of cancer cells, whereas excessive accumulation of ROS can lead to various forms of programmed cell death—including ferroptosis and apoptosis—making ROS potential therapeutic targets in cancer treatment. EC is the most common gynecologic malignancy in developed countries, and its global incidence and mortality rates have been steadily increasing. Although significant research has been conducted on the etiology and treatment of EC, progress remains limited. Thus, further exploration of the role of ROS in the pathogenesis of EC is warranted. In this study, we conducted a literature review using databases including the Cochrane Library, EMBASE, Google Scholar, PubMed, and SCOPUS with the search terms “endometrial cancer” and “nitric oxide.” Of the 142 identified articles, 18 were selected for detailed review. The analysis revealed that ROS contributes to EC progression through mechanisms such as DNA damage and genomic instability, interactions with estrogen and progesterone signaling, and immune dysregulation. Potential therapeutic agents targeting ROS identified in the literature include hinokitiol, α-terthienylmethanol, ellipticine, fructose-1,6-bisphosphate, oleanolic acid 3-acetate, CaBP-28 k, simvastatin, and amentoflavone. These findings suggest that oxidative stress plays a critical role in the progression of EC. A deeper understanding of ROS regulatory mechanisms may open new avenues for the development of targeted therapies for EC.